Aplikasi Bursa Kerja Alumni STMIK Ichsan Gorontalo Berbasis Website : Aplikasi Bursa Kerja Alumni STMIK Ichsan Gorontalo Berbasis Website - citra Yustitya gobel; Santawali (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2022)
The quality of a college graduate depends on how quickly the student gets the first job, and how much the first salary is earned. The purpose of this study is to make it easier for STMIK Ichsan Gorontalo alumni to get a job quickly and make it easier for companies to inform job vacancies and Designing Information Systems Stock Exchange for STMIK-based alumni Web where job seekers are graduates and job providers can be able to communicate quickly with each other . Based on the discussion it can be concluded that the results of this application design can help the Alumni STMIK Ichsan Gorontalo in the process of finding work quickly with valid information from job seeker company.and Information System Working Exchange is made with simple governance and can facilitate job seekers in providing information job vacancy to alumni STMIK Ichsan Gorontalo in accordance with the fields required by the company